2007
DOI: 10.1248/bpb.30.1102
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nitric Oxide in Radiation Damage

Abstract: Free radicals, such as hydrogen and hydroxyl radicals, are produced in aqueous solution after X-irradiation. 1) They react with body tissues and generate lipid peroxidation, DNA lesions and enzyme inactivation, all of which are mediators of radiation damage. [2][3][4][5] Nitric oxide is another free radical induced by irradiation.6,7) Nitric oxide induces vasorelaxation and inhibition of platelet aggregation and thus, can improve hypertension or prevent thrombosis. In contrast, nitric oxide can also have cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 29 publications
2
17
0
2
Order By: Relevance
“…The increase of NO production in irradiated macrophages contributed to tumoricidal activity, with the activation mechanisms differing between high-dose and low-dose irradiation. Our results also in agreement with Ohata et al [31] who investigated the role of nitric oxide in relation to radiation damage, by examining changes in mouse serum nitrate concentrations after irradiation. They reported that post-irradiation serum nitrate concentrations increased dose-dependently with radiation dose, and, claim the known physiological functions of nitric oxide imply that it should prevent radiation-induced death.…”
Section: Parameterssupporting
confidence: 92%
“…The increase of NO production in irradiated macrophages contributed to tumoricidal activity, with the activation mechanisms differing between high-dose and low-dose irradiation. Our results also in agreement with Ohata et al [31] who investigated the role of nitric oxide in relation to radiation damage, by examining changes in mouse serum nitrate concentrations after irradiation. They reported that post-irradiation serum nitrate concentrations increased dose-dependently with radiation dose, and, claim the known physiological functions of nitric oxide imply that it should prevent radiation-induced death.…”
Section: Parameterssupporting
confidence: 92%
“…Thus an alternative explanation must be sought. It was reported that γ irradiation of mice results in a statistically significant two- to threefold increase in serum nitrate concentration 2.5–3.0 h postirradiation that returns to baseline after 12 h (32). This nitrate increase is consistent with the effect in mice of sublethal γ -radiation exposure on nitric oxide (NO) synthesis in the liver, intestine, lung, kidney, brain, spleen and heart (33), on increased hepatic nitrite concentration and peroxidative damage (34), and on attenuated hepatic glutathione concentration (34, 35).…”
Section: Discussionmentioning
confidence: 99%
“…11 However, studies using iNOS inducers and NOS inhibitors indicate that elevated NO production can also contribute to radiation injury. 12 Furthermore, NOS2 gene transfer into tumors increased their radiosensitivity, 13 and NOS1-null mice show increased radioresistance in bone marrow.…”
mentioning
confidence: 99%